Management and organisational behaviour : contemporary challenges and future directions - Wiesner, Retha; Millett, Bruce (J. Wiley, 2000)
Organisational behaviour and the contemporary environment. Managing individuals in organisations. Managing groups in organisations. Managing organisations. Managing the processes of organisational behaviour. Managing organisational dynamics.